PERLINDUNGAN DATA PRIBADI DALAM PENGGUNAAN APLIKASI PEDULILINDUNGI SELAMA PANDEMI COVID-19 - Arif Wahyu Hidayat (Jurnal Magister Hukum Perspektif, 2020)
Several countries in the world including Indonesia are experiencing the COVID-19 pandemic. A series of efforts to prevent the spread of COVID-19 were carried out. One such effort is the launch of the Pedulilindungi application which serves to track every possible transmission that exists. The basis of the launch of the application is the Decree of the Minister of Communication and Informatics Number 171 of 2020 concerning the Determination of Application for Care and Protection in the Framework of The Implementation of Health Surveillance for the Handling of Corona Virus Disease 2019 (COVID-19). The purpose of this study is to find out the security risks of Pedulilindungi applications and how the ITE Law accommodates the security of personal data from the use of applications. The research method used is a normative research method. The results showed that the use of the Pedulilindungi application has the potential to cause a breach of personal data security stipulated in the ITE Law. Access to data stored in the user's mobile device data is not clearly notified to the user during use in everyday life. In addition, this application also does not mention who can access and process the data in question. The vagueness of the rules will arise when the pandemic ends, whether personal data will automatically be deleted or not, considering that the function of this application is only intended when facing the COVID-19 pandemic. Keywords: COVID-19 pandemic, protection of personal data, Pedulilindungi